An Analysis of Three Dimensional Aspects Reflected in the Movie Entitled “Barbie” - Kania Maharani, Ni Putu; Gde Nova Winarta , Ida Bagus (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
The study focused ot find out three dimensional aspects in the movie entiled Barbie (2023). The movie produced by Greta Gerwig and written by Noah Baumbach. The story is about the stereotypical Barbie as a fellow dolls resident in Barbieland. She lives with Ken and other differents barbie dolls. Then, while kens spend their playing at the beach, considering it their profession, the Barbie hold prestigious job such as doctor. Beach Ken ("Ken") is only happy when he has deep relationship with her, but she rebuffs him in favor of other activities. the method of this research is descriptive qualitative method. The author following several steps to get data: 1) Watching the movie to get main point, 2) Read English subtitle based of the movie, 3) Taking-note of the dialogue, and 4) Identify three-dimensional aspect of main or supporting characters. This result show that the main character has three dimensional aspects such as psychological, sociological, and physiological dimension. These main character and supporting character has three dimensional aspect depends on situation surrounding themselves, that also helo her/his characters could change. On the other hand, three dimensional aspect that influences main characters or supporting characters to making decision in their life.